The export economies : their pattern of development in historical perspective - Levin, Jonathan Victor; Harvard Law School (Cambridge, Massachusetts : Harvard University Press, 1960)
This book explores the strategic facts and relations in the pattern of all export economies development and clothes this analysis with case studies.
Includes bibliographical references and index
ijb 16/01/2019
Loans
Keywords: Commerce; Exports; Developing countries; Peru; Burma